Endoscopic management of gastrointestinal motility disorders – part 2: European Society of Gastrointestinal Endoscopy (ESGE) Guideline - Weusten, Bas L. A. M.; Barret, Maximilien; Bredenoord, Albert J.; Familiari, Pietro; Gonzalez, Jean-Michel; van Hooft, Jeanin E.; Lorenzo-Zúñiga, Vicente; Louis, Hubert; Martinek, Jan; van Meer, Suzanne; Neumann, Helmut; Pohl, Daniel; Prat, Frederic; von Renteln, Daniel; Savarino, Edoardo; Sweis, Rami; Tack, Jan; Tutuian, Radu; Ishaq, Sauid (Endoscopy, 2020)
ESGE suggests flexible endoscopic treatment over open surgical treatment as first-line therapy for patients with a symptomatic Zenker’s diverticulum of any size.Weak recommendation, low quality of evidence, level of agreement 100 %.ESGE recommends that emerging treatments for Zenker’s diverticulum, such as Zenker’s peroral endoscopic myotomy (Z-POEM) and tunneling, be considered as experimental; these treatments should be offered in a research setting only.Strong recommendation, low quality of evidence, level of agreement 100 %.ESGE recommends against the widespread clinical use of transoral incisionless fundoplication (TIF) as an alternative to proton pump inhibitor (PPI) therapy or antireflux surgery in the treatment of gastroesophageal reflux disease (GERD), because of the lack of data on the long-term outcomes, the inferiority of TIF to fundoplication, and its modest efficacy in only highly selected patients. TIF may have a role for patients with mild GERD who are not willing to take PPIs or undergo antireflux surgery.Strong recommendation, moderate quality of evidence, level of agreement 92.8 %.ESGE recommends against the use of the Medigus ultrasonic surgical endostapler (MUSE) in clinical practice because of insufficient data showing its effectiveness and safety in patients with GERD. MUSE should be used in clinical trials only.Strong recommendation, low quality evidence, level of agreement 100 %.ESGE recommends against the use of antireflux mucosectomy (ARMS) in routine clinical practice in the treatment of GERD because of the lack of data and its potential complications.Strong recommendation, low quality evidence, level of agreement 100 %.ESGE recommends endoscopic cecostomy only after conservative management with medical therapies or retrograde lavage has failed.Strong recommendation, low quality evidence, level of agreement 93.3 %.ESGE recommends fixing the cecum to the abdominal wall at three points (using T-anchors, a double-needle suturing device, or laparoscopic fixation) to prevent leaks and infectious adverse events, whatever percutaneous endoscopic cecostomy method is used.Strong recommendation, very low quality evidence, level of agreement 86.7 %.ESGE recommends considering endoscopic decompression of the colon in patients with Ogilvie’s syndrome that is not improving with conservative treatment.Strong recommendation, low quality evidence, level of agreement 93.8 %.ESGE recommends prompt endoscopic decompression if the cecal diameter is > 12 cm and if the Ogilvie’s syndrome exists for a duration of longer than 4 – 6 days.Strong recommendation, low quality evidence, level of agreement 87.5 %.